Penerapan Metode Bermain Peran Berdukungan Media Audiovisual untuk Menanamkan Sikap Sopan Santun pada Siswa Sekolah Dasar - Hefi Rusnita Dewi; Hatijah Hatijah (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstrak: Application of Audiovisual Media-Enabled Role-Playing Methods to Instill An Attitude of Manners in Students sekolah dasar. This study aims to determine the use of role-playing methods supported by audiovisual media to instill an attitude of manners in elementary school students. The role-playing method using audio-visual media is a way of presenting a topic or subject matter by showing, demonstrating or representing circumstances or events experienced by people such as or behaviors in social relationships based on learning from videos. This type of research is descriptive with quantitative. questionnaires and observation sheets The results of this study are described as follows: (1) The politeness of self-assessment before and after treatment is improved based on performance analysis with learning methods. An effective role-playing method that teaches students an attitude of manners, this is reflected in N-Gain, self-assessment of manners attitude increased by 0.79 in the high category. (2) Student response results in general are in the category of tending to be positive with an average of 2.69. (3) Student activity from the average of all aspects observed was 83.5 was in the good category (4) the implementation of P encana P implementation P was in the category of very well carried out with an average score of 4.3. It can be concluded that learning through role-playing methods supported by audiovisual media is effective inteaching the manners of elementary school students.